Local government internal auditor stress and burnout: Supervisor support as a moderating variable - Novriansa, Agil; Muthia, Fida (Badan Pemeriksa Keuangan Republik Indonesia, 2023)
This study aims to empirically examine the direct relationship between stress arousal and burnout and the moderating effect of supervisor support on the relationship between the two dimensions experienced by local government internal auditors. This study uses an online survey method with a questionnaire. The sample for this study was 155 local government internal auditors from 17 City/Regency Government Inspectorate Provinces from Southern Sumatra. Based on the data analysis using SEM-PLS, the results of this study indicate that stress arousal is positively related to emotional exhaustion and depersonalization but not to reduced personal accomplishment. The results of this study also indicate that supervisor support is able to moderate the relationship between stress arousal and burnout. Supervisor support can reduce the effects of stress arousal on emotional exhaustion and depersonalization experienced by local government internal auditors and strengthen the effects of stress on personal accomplishment. Theoretically, this study supports the conservation of resources theory, which shows that supervisor support is a resource that acts as an effective coping strategy in reducing the effects of stress arousal and preventing burnout. The results also provide insights for policymakers to develop interventions for communication and monitoring based on personal conditions to improve interpersonal relations between supervisors and subordinates.